Transitional multilingual education policies in Africa: necessary compromise or strategic impediment?. (4th May 2019) - Odugu, Desmond I.; Lemieux, Camille N.
Abstract: Despite advances in multilingual education (MLE) scholarship, education in most African societies remain characteristically congruent with colonial normative monolingual and transitional multilingual policies, which limit the use of native language(s) as media of instruction to early primary schooling. This contributes to poor educational and social outcomes far below the projected benefits of MLE. Convinced that the complex relationships between language and education have been discerned, MLE scholarship has become increasingly advocacy oriented to corresponding policies and practices, with purportedly widespread resistance from parents, policymakers, and educators. This focused ethnographic inquiry into the perspectives of parents, educators, researchers, and policymakers on MLE finds mixed messages in MLE advocacy that foment localized resistance to and disincentivize full native language-based MLE (NLB-MLE) policy changes. Specifically, transitional multilingualism, a compromise with NLB-MLE opposition, entails inherent instrumentality and linguistic hierarchy, which undermines the fundamental principles of linguistic and cultural diversity that is the hallmark of NLB-MLE. Considering the colonial, political, and scientific sources of transitional multilingualism, the findings support a reconfiguration of the intellectual anchorage, social agenda, and discursive scope of MLE scholarship to address the strategic challenge, which transitional multilingualism poses to NLB-MLE policy shift and its pedagogical and cultural promises.